2007
DOI: 10.1177/0961203307079454
|View full text |Cite
|
Sign up to set email alerts
|

A study of association of the complement C4 mutations with systemic lupus erythematosus in the Malaysian population

Abstract: The aim of the present study was to investigate the association of C4 gene mutations with systemic lupus erythematosus, in 130 Malaysian SLE patients and 130 healthy controls. Generally, various PCR approaches were used to screen the mutations of the C4 genes, which included 2 bp (+TC) insertions at codon 1213 in exon 29, 1 bp deletions (-C) at codon 811 in exon 20, 1 bp (-C), 2 bp (-GT) deletions at codons 522 and 497 in exon 13 and null alleles. No mutations located at exons 13, 20 and 29 of the C4 gene, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3. 39 Most studies of TAP genes have produced negative results in Colombians, Australians and Asians including Japanese and Chinese, 7,[40][41][42][43] but the TAP-2 gene showed a positive result in a Colombian population.…”
Section: Resultsmentioning
confidence: 99%
“…35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3. 39 Most studies of TAP genes have produced negative results in Colombians, Australians and Asians including Japanese and Chinese, 7,[40][41][42][43] but the TAP-2 gene showed a positive result in a Colombian population.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the important target genes such as C4, C1q, CTLA-4, IL-6, IL-1, RANTES-28, and SDF-1 have been studied previously in the Malaysian population (Puah et al, 2007;Chew et al, 2008;Chua et al, 2009aChua et al, ,b, 2010Lian et al, 2011); however, most of them were found to have no major significant association with SLE susceptibility. Hence in this study, we aimed to target and investigate the distribution of the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) dimorphism and its potential association to the susceptibility of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…A conventional DNA extraction method (Puah et al, 2007;Chua et al, 2009b;Chua et al 2011b) was used to isolate the genomic DNA from whole blood samples. All samples were then screened for the Arg702Trp, Gly908Arg, 3020insC, Pro268Ser, and JW1 variants by using the TaqMan SNP Genotyping Assay (Applied Biosystems, USA) as shown in Table 1.…”
Section: Genotyping Of the Nod2/card15 Variantsmentioning
confidence: 99%